Long COVID in Children: A Call for Paying More Attention - Limal, Clément (Science Insights, 2024)
Long COVID in pediatric patients has lately attracted the interest of healthcare professionals and researchers around. Children, although typically less susceptible to severe sickness caused by the virus, can still have enduring symptoms such as weariness, impaired concentration, and respiratory problems long after their first infection. Acknowledging and dealing with these persistent consequences is essential to guaranteeing the general health and welfare of pediatric patients. Healthcare practitioners need to dedicate more focus to the phenomena of Long COVID in children, undertaking additional research to comprehend its frequency, risk factors, and best therapies. By enhancing knowledge and executing customized interventions for those impacted, we can more effectively facilitate the process of recovery and enhance results for this susceptible group.